2011
DOI: 10.1160/th10-12-0782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified thromboelastography assay for the screening of von Willebrand disease

Abstract: Thromboelastography (TEG) has been shown to be a valuable point-of-care device for the rapid diagnosis of various bleeding disorders. However, TEG has thus far not been used for the screening for von Willebrand disease (VWD). We evaluated the performance of a modified TEG assay for the laboratory screening of VWD. Three hundred twenty-eight patients (148 male, 180 female, median age 8.4 years, range 0.1 - 72.7 years) were included in the study. The diagnosis and classification of patients was based on personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…For normal persons, addition of ristocetin lowered clot strength because the agglutination of platelets removed platelets from the coagulation cascade. In patients with vWD, the TEG traces were only slightly inhibited because addition of ristocetin did not affect platelets because of the lack of vWF . This technique demonstrates the importance of platelets in maintaining clot mechanical properties and shows how the understanding of clot mechanical properties can be exploited to diagnose blood disorders.…”
Section: Macroscale Biomechanics In Haemostasismentioning
confidence: 88%
See 2 more Smart Citations
“…For normal persons, addition of ristocetin lowered clot strength because the agglutination of platelets removed platelets from the coagulation cascade. In patients with vWD, the TEG traces were only slightly inhibited because addition of ristocetin did not affect platelets because of the lack of vWF . This technique demonstrates the importance of platelets in maintaining clot mechanical properties and shows how the understanding of clot mechanical properties can be exploited to diagnose blood disorders.…”
Section: Macroscale Biomechanics In Haemostasismentioning
confidence: 88%
“…Type II results from qualitative deficiencies, and is split into Type 2A, 2B, 2M and 2N. Type III is a quantitative deficiency, although vWF is nearly absent in the blood in these patients . Ristocetin is an antibiotic that causes vWF to bind to platelets, resulting in platelet agglutination.…”
Section: Macroscale Biomechanics In Haemostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The applications of TEG have expanded greatly over the past 5 years with substantial attention given to standardization [13][14][15][16]. A recent report has shown evidence for TEG as a screening tool in VWD [17] and indicated that maximum amplitude (MA) is related to VWF:RCo. However, there have been no reports/data regarding the use of TEG in type 2B VWD.…”
Section: Sirmentioning
confidence: 99%
“…In diesem Sinne kann beispielsweise durch eine spezielle Titrationstechnik auch ein Protamineffekt oder ein Hirudineffekt [28] mittels der Rotationsthrombelastometrie abgeschätzt werden. Kürz-lich wurde sogar ein Ansatz zur Erfassung eines Willebrand-Syndroms beschrieben [30]. Bisher haben diese speziell modifizierten thrombelastometrischen Ansätze jedoch keinen Eingang in den klinischen Alltag gefunden.…”
Section: Spezielle Fragestellungenunclassified